Efektivitas Live Streaming, Content Marketing dan Brand Trust terhadap Keputusan Pembelian Viva Cosmetic di Bisnis Marketplace Tiktokshop - Al Machfudz WDP; Indayani, Lilik (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to find out and measure how much influence Live Streaming, Content Marketing and Brand Trust have on Viva cosmetic purchasing decisions in the TikTokshop marketplace business. This research is quantitative research that uses an explanatory research approach. The population in this study was taken from Viva Cosmestic consumers in the TikTokshop e-commerce business. The sample obtained was 100 respondents using a non-probability sampling technique using the lemeshow formula. Data collection in this research was by observation and distributing questionnaires which were measured using a Likert scale. This research uses the SPSS analysis method. The results of this research prove that Live Streaming influences purchasing decisions. Content Marketing influences purchasing decisions. Brand Trust influences purchasing decisions. Thus, it can be concluded that Live Streaming, Content Marketing, Brand Trust have a simultaneous influence on purchasing decisions